Turner syndrome and autoimmune diseases: record-linkage study - Goldacre, M; Seminog, O (2014)
Background: There is increasing evidence that Turner syndrome is associated with an elevated risk of a range of autoimmune disorders. We aimed to document this in a national study. Method: Use of a record-linked dataset of all hospital admissions in England, 1999-2011, to construct a retrospective cohort of people with Turner syndrome and a control cohort of people without it. Statistical follow-up to identify the occurrence of 29 separate autoimmune disorders in each cohort. Calculation of rate ratios, comparing the Turner and control cohorts. Results: In the Turner syndrome cohort (2459 people), rate ratios were elevated for 16 of the 29 conditions. Examples included coeliac disease (rate ratio 14.0, 95% CI 10.2 to 18.8), Crohn's disease (5.3, 3.5 to 7.8), ulcerative colitis (3.9, 2.3 to 6.1), hypothyroidism (8.8, 7.8 to 9.9) and hyperthyroidism (4.9, 3.2 to 7.1). Conclusions: The increased risk of autoimmune disorders in people with Turner syndrome covers a wide range of conditions.